2011
DOI: 10.4137/ccrpm.s6437
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension in Patients with Treated Pulmonary Tuberculosis: Analysis of 14 Consecutive Cases

Abstract: Background:Pulmonary tuberculosis (PTB) is an increasing global health problem that continues to cause significant morbidity and mortality. The impact of PTB has been measured in terms morbidity and mortality and little attention has been paid to continuing respiratory disability in those who were cured. Pulmonary hypertension (PHT) is a serious respiratory disability that results from structural lung damage and chronic hypoxia. This study was conducted to investigate the presence of PHT in a cohort of treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 15 publications
0
38
1
Order By: Relevance
“…Another study from Egypt found a PH prevalence of 9% in patients seropositive for schistosomal antibodies. Ahmed et al 18 from Sudan described 14 consecutive cases of PH with previously treated pulmonary TB and concluded that PH can even occur after resolution of TB, most likely due to persistent lung destruction. These data suggest that left heart disease, chronic lung disease, RHD, HIV, schistosomiasis and SCD might be the most common underlying diseases to cause PH within the spectrum of aetiologies of PH that we will find within the Pan African Pulmonary hypertension Cohort (PAPUCO)…”
Section: Introductionmentioning
confidence: 99%
“…Another study from Egypt found a PH prevalence of 9% in patients seropositive for schistosomal antibodies. Ahmed et al 18 from Sudan described 14 consecutive cases of PH with previously treated pulmonary TB and concluded that PH can even occur after resolution of TB, most likely due to persistent lung destruction. These data suggest that left heart disease, chronic lung disease, RHD, HIV, schistosomiasis and SCD might be the most common underlying diseases to cause PH within the spectrum of aetiologies of PH that we will find within the Pan African Pulmonary hypertension Cohort (PAPUCO)…”
Section: Introductionmentioning
confidence: 99%
“…This is comparable to the median age of 43 years in a study on PAH in patients with post-TB-sequelae by Ahmed et al . [25] Thus, patients developing PAH as sequelae of TB are younger than patients developing PAH secondary to chronic obstructive airway disease (median age 66 years). [26] In our study, there were significant differences in the median TMS and TLS in patients with or without pulmonary artery dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with the study by Ahmed et al . [25] in which fibrocavitary disease was seen in 50% of patients with PAH due to PTB sequelae. Development of PAH in post-TB sequelae has been attributed to both structural lung damage and repeated secondary infections.…”
Section: Discussionmentioning
confidence: 99%
“…For example, pulmonary tuberculosis oen leads to PAH [122][123][124] and not to, surprisingly, tuberculosis produces substantial elevation of much of the in�amma-tory cascade, including elevation of NF-B in�ammatory cytokines, iNOS induction, NO, and the marker of peroxynitrite (ONOO − ), 3-nitrotyrosine [125].…”
Section: Principlementioning
confidence: 99%